2018
DOI: 10.1080/14779072.2018.1475231
|View full text |Cite
|
Sign up to set email alerts
|

Primary prevention of post-pericardiotomy syndrome using corticosteroids: a systematic review

Abstract: Post-pericardiotomy syndrome is a well-recognized inflammatory phenomenon that commonly occurs in patients following cardiac surgery. Due to the increased morbidity and resource utilization associated with this condition, research has recently focused on ways of preventing its prevention this condition; primarily using colchicine, NSAIDs and corticosteroids. Areas covered: This systematic review summarizes the three clinical studies that have used corticosteroids for PPS primary prevention in the perioperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
0
2
1
4
Order By: Relevance
“…TNFα levels vs other cytokines rise early that reflects its role as an initiator in the inflammatory response. TNFα is a mediator of various pathologies and involved in the "cytokine storm" [14]. The results of our study revealed no signi ficant inter-group differences in serum IL-1β levels, as well as significant changes in IL-1β between follow-up stages.…”
Section: Resultscontrasting
confidence: 48%
“…TNFα levels vs other cytokines rise early that reflects its role as an initiator in the inflammatory response. TNFα is a mediator of various pathologies and involved in the "cytokine storm" [14]. The results of our study revealed no signi ficant inter-group differences in serum IL-1β levels, as well as significant changes in IL-1β between follow-up stages.…”
Section: Resultscontrasting
confidence: 48%
“…On the other hand, a retrospective study including overall 200 adult patients reported significant PPS reduction in patients receiving a single intraoperative dose of 1 mg/kg methylprednisolone (22.0% vs. 37.0%, p < 0.026) [79]. It has been suggested that the positive result conflicting with previous studies could be due to the strict exclusion criteria used [186]. Further large-scale studies are needed to assess the possible value of corticosteroids in the prevention of PPS maintaining special focus on the exact timing and route of the drug administration [186].…”
Section: Preventionmentioning
confidence: 95%
“…It has been suggested that the positive result conflicting with previous studies could be due to the strict exclusion criteria used [186]. Further large-scale studies are needed to assess the possible value of corticosteroids in the prevention of PPS maintaining special focus on the exact timing and route of the drug administration [186].…”
Section: Preventionmentioning
confidence: 99%
“…Вместе с тем, достоверных данных об эффективности назначения стероидных препаратов (дексаметазон в дозе 1 мг/кг) в предоперационном периоде не получено [2,14]. Наряду с этим, назначение колхицина приводило к снижению вероятности развития рецидивирующего перикардита в послеоперационном периоде [1,9].…”
Section: материал и методыunclassified
“…Рост хирургической активности и сложности выполняемых операций на открытом сердце диктует необходимость выявления предикторов развития, совершенствования методов ранней диагностики и разработки новых подходов к профилактике одного из самых частых осложнений кардиохирургического вмешательства постперикардиотомного синдрома (ПКТС), который регистрируется у 9-65% больных [1][2][3]. Наряду с операциями на открытом сердце, развитие ПКТС описано при эндоваскулярных вмешательствах, таких как чрескожная коронарная ангиопластика со стентированием, радиочастотная катетерная аблация сердца, имплантация внутрисердечных устройств [4,5].…”
unclassified